Lesson Learned Health Information System of Taiwan Leprosy Control Program for Indonesia Leprosy Control Program - Enny Rachmani (979-26-0263-1)
Background of study: Indonesia is the three biggest endemic areas after Indiaand Brazil. In 2010, had been reported 19.785 registered prevalence, 17.012 newcases and 1.822 the new case found with grade-2 disabilities [2]. Utilization oftechnology in Leprosy Control Program was not maximize in developing countriesinclude Indonesia although there were many cases. It posed a lot of problem inthat program such as Drop out MDT (Multi Drug Treatment) treatment becausedifficulties in monitoring, difficult to conduct active case finding, and difficult tomake timely report. Taiwan is one of the areas which already had eradication inleprosy; all new cases came from foreigner from epidemic countries [3]. Taiwanalso one of the best implementor of health information system in the world so itnecessary to learn how leprosy control program and implementation of healthinformation system in Taiwan to develop Indonesia leprosy control program andmaximize computerize of Leprosy Control Program in Indonesia.Method: Data collections in this research through deep interview to 3 staff districtleprosy supervisor in Disease Control Officer of Health Office of PekalonganDistrict and also 3 staff Control Disease Center (CDC) in Taipei. This researchalso made observation in information system of leprosy Control Program inIndonesia and TaipeiResult: In Taiwan, there are a drug observer and a public health nurse toobserve patient treatment. This system made simple to monitor complete ofpatient treatment, and beside that regulation in Taiwan can drive patient to finishtheir treatment. Indonesia also using drug observer system but just in TBProgram called DOTS (Directly Observer Treatment, Short Course). Taiwan didnot have difficulties in continuity and availability of leprosy data because theyhave been using information system to store data and reporting system.Indonesia still had that problem because of a rotation system in civil servantswork environment. Taiwan Leprosy information system through National IDconnected patient with their contact so it very easy to contact trace to blockdevelop new case in Taiwan, Indonesia Leprosy electronic application have beenimplemented it was just registry patient to make report; it must be augment tooptimize the effectiveness leprosy control program in Indonesia.From Taiwan experience in leprosy control systems, Indonesia can learned thatdrug observer and information system play important role to prevent develop newcase through trace contact and monitoring MDT treatment. The recent ofIndonesia Leprosy electronic application should be build up with databasemanagement system for easier retrieve information and keep the data safely andstore in a long time.